Chromosome-level genome assembly of the Muscovy duck provides insight into fatty liver susceptibility - Xu, Ming-Min; Gu, Li-Hong; Lv, Wan-Yue; Duan, Sheng-Chang; Li, Lian-Wei; Du, Yuan; Lu, Li-Zhi; Zeng, Tao; Hou, Zhuo-Cheng; Ma, Zhanshan Sam; Chen, Wei; Adeola, A.C.; et al. (Elsevier, 2022)
The Muscovy duck (Cairina moschata) is an economically important poultry species, which is susceptible to fatty liver. Thus, the Muscovy duck may serve as an excellent candidate animal model of non-alcoholic fatty liver disease. However, the mechanisms underlying fatty liver development in this species are poorly understood. In this study, we report a chromosome-level genome assembly of the Muscovy duck, with a contig N50 of 11.8 Mb and scaffold N50 of 83.16 Mb. The susceptibility of Muscovy duck to fatty liver was mainly attributed to weak lipid catabolism capabilities (fatty acid β-oxidation and lipolysis). Furthermore, conserved noncoding elements (CNEs) showing accelerated evolution contributed to fatty liver formation by down-regulating the expression of genes involved in hepatic lipid catabolism. We propose that the susceptibility of Muscovy duck to fatty liver is an evolutionary by-product. In conclusion, this study revealed the potential mechanisms underlying the susceptibility of Muscovy duck to fatty liver.